Kinetic analysis of Polyethylene Terephthalate (PET) by using TGA: article - Rosdi, Muhammad Ridzwan; Alias, Rusmi (2019)
This study provides the effect of temperature on mass change of plastic over time by using Thermogravimetric Analysis (TGA).The main objectives includes studying the thermal degradation and kinetic analysis of 20mg plastic Polyethylene terephthalate (PET). Thermal degradation was done by using a Thermogravimetric analyzer with temperature range from 25°C to 800°C at varies heating rates. Calculated kinetics parameters obtained by using Ozawa Flynn and wall (OFW) method are 86.764 KJ/mol for the activation energy (Ea) and 1.29x1010 min -1 for the pre exponential factor (A).